Modeling of laser speckles of heterogeneous dynamics in drying and aging paint dispersions using a view-based temporal template method. (7th June 2018) - Ansari, M Z; Mujeeb, A
Abstract: Assessments of the microscopic mechanism underlying the phenomenon of drying and aging of various paint dispersions are important for the requirements of sustainable and high-quality paints. The present work demonstrates the application of the motion history image (MHI) algorithm to visualize the microscopic mechanisms during drying and aging of different paints dispersions. We assessed the micromechanical dynamics of the drying process on laser speckle imaging data after generating the MHI maps. The processes such as cracking and delamination of paint on a glass substrate and the flow of an imbibition front on a porous substrate were analyzed using the MHI analysis, which identifies the locations where the phenomenon evolves with time.